Integrated transcriptomic and metabolic analyses provide insights into the maintenance of embryogenic potential and the biosynthesis of phenolic acids and flavonoids involving transcription factors in Larix kaempferi (Lamb.) Carr. - Wang, Junchen; Zhang, Lifeng; Qi, Liwang; Zhang, Shougong (Frontiers in Plant Science, 2022)
The frequent occurrence of non-embryogenic callus (NEC) during embryogenic callus (EC) induction has impose constraints on the application of somatic embryogenesis (SE) in Larix kaempferi (Lamb.) Carr. In this study, integrated transcriptomic and metabolomic analyses were performed in EC and NEC originating from a single immature zygotic embryo to better decipher the key molecular and metabolic mechanisms required for embryogenic potential maintenance. The results showed that a total of 13,842 differentially expressed genes (DEGs) were found in EC and NEC, among which many were enriched in plant hormone signal transduction, starch and sucrose metabolism, phenylpropanoid biosynthesis, flavonoid biosynthesis, and the biosynthesis of amino acids pathways. Metabolite profiling showed that 441 differentially accumulated metabolites (DAMs) were identified in EC and NEC. Both EC and NEC had vigorous primary metabolic activities, while most secondary metabolites were upregulated in NEC. Many totipotency-related transcription factor (TF) genes such as BBMs, WUSs, and LEC1 showed higher expression levels in EC compared with NEC, which may result in the higher accumulation of indole 3-acetic acid (IAA) in EC. NEC was characterized by upregulation of genes and metabolites associated with stress responses, such as DEGs involved in jasmonic acid (JA) and ethylene (ETH) biosynthesis and signal transduction pathways, and DEGs and DAMs related to phenylpropanoid and flavonoid biosynthesis. We predicted and analyzed TFs that could target several key co-expressed structural DEGs including two C4H genes, two CcoAOMT genes and three HCT genes involved in phenylpropanoid and flavonoid biosynthesis. Based on the targeted relationship and the co-expression network, two ERFs (Lk23436 and Lk458687), one MYB (Lk34626) and one C2C2-dof (Lk37167) may play an important role in regulating phenolic acid and flavonoid biosynthesis by transcriptionally regulating the expression of these structural genes. This study shows an approach involving integrated transcriptomic and metabolic analyses to obtain insights into molecular events underlying embryogenic potential maintenance and the biosynthesis mechanisms of key metabolites involving TF regulation.